Changes in Prudential Policy Instruments : A New Cross-Country Database - Cerutti, Eugenio (IMF Working Papers; Working Paper ;, 2016)
This paper documents the features of a new database that focuses on changes in the intensity in the usage of several widely used prudential tools, taking into account both macro-prudential and micro-prudential objectives. The database coverage is broad, spanning 64 countries, and with quarterly data for the period 2000Q1 through 2014Q4. The five types of prudential instruments in the database are: capital buffers, interbank exposure limits, concentration limits, loan to value (LTV) ratio limits, and reserve requirements. A total of nine prudential tools are constructed since some useful further decompositions are presented, with capital buffers divided into four subindices: general capital requirements, real state credit specific capital buffers, consumer credit specific capital buffers, and other specific capital buffers; and with reserve requirements divided into two sub-indices: domestic currency capital requirements and foreign currency capital requirements. While general capital requirements have the most changes from the cross-country perspective, LTV ratio limits and reserve requirements have the largest number of tightening and loosening episodes. We also analyze the instruments' usage in relation to the evolution of key variables such as credit, policy rates, and house prices, finding substantial differences in the patterns of loosening or tightening of instruments in relation to business and financial cycles.